Предмет: Алгебра,
автор: йхэфяю
Напишите подробное доказательство!!! Очень нужно!!!!
Приложения:
Ответы
Автор ответа:
0
(tgα+ctgα)*(1-cos(4α)=
=(sinα/cosα+cosα/sinα)*(sin²(2α)+cos²(2α)-cos²(2α)+sin²(2α))=
=((sin²α+cos²α)/(sinα*cosα))*2*sin²(2α)=
=(1/(sinα*cosα))*2*sin²(2α)=(2/(2*sinα*cosα))*2*sin²(2α)=
=4*sin²(2α)/sin(2α)≡4*sin(2α).
=(sinα/cosα+cosα/sinα)*(sin²(2α)+cos²(2α)-cos²(2α)+sin²(2α))=
=((sin²α+cos²α)/(sinα*cosα))*2*sin²(2α)=
=(1/(sinα*cosα))*2*sin²(2α)=(2/(2*sinα*cosα))*2*sin²(2α)=
=4*sin²(2α)/sin(2α)≡4*sin(2α).
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Физика,
автор: 19plohoi
Предмет: Українська мова,
автор: svirgunevelina
Предмет: Математика,
автор: kea7419
Предмет: Математика,
автор: hz12